Comprehensive transcriptome and proteome analysis revealed the molecular mechanisms of melatonin priming and waterlogging response in peach - Gu, Xianbin; Lu, Linghong; Gao, Jing; Fan, Fei; Song, Genhua; Zhang, Huiqin (Frontiers in Plant Science, 2025)
Waterlogging substantially hampers the growth and development of plants. The escalating trajectory of global climate change is heightening both the frequency and intensity of waterlogging events. Peach trees are particularly vulnerable to waterlogging, with the resultant hypoxia in the rhizosphere profoundly influencing their growth and productivity. This study explored the responses of peach seedlings to waterlogging and the regulatory effects of melatonin priming. After a 24-h waterlogging treatment, a significant increase in relative electrical conductivity and an accumulation of reactive oxygen species were observed, ion permeability was markedly alleviated by melatonin priming. Transcriptomic and proteomic analyses were conducted on peach root samples to elucidate the molecular mechanisms involved in the response to waterlogging and melatonin priming. Transcriptome analysis implicated genes related to ‘DNA-binding transcription factor activity’, such as AP2/ERF, HSF and WRKY transcription factors, in response to waterlogging. The glycolysis/gluconeogenesis pathway was also significantly enriched, indicating its critical role in the metabolic response to waterlogging. A correlation analysis between differentially expressed genes and proteins highlighted the regulation of numerous genes at both the transcriptional and translational levels. Furthermore, core DEGs/DEPs, including heat shock proteins and stress-related proteins, were identified. Notably, ERF VII member ERF071 (Prupe.8G264900), ADH (Prupe.8G018100), and PCO (Prupe.7G011000) emerged as potential targets for genetic manipulation to enhance waterlogging tolerance in peach. This research provides targets for breeding waterlogging-tolerant varieties and strategies to mitigate waterlogging stress in peach.